2001
DOI: 10.1001/archpedi.155.5.597
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of Smoking Prevention and Cessation Services to Adolescents

Abstract: Familiarity with smoking cessation guidelines and physician's specialty and practice style with adolescents are associated with better delivery of tobacco cessation counseling to adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 20 publications
1
24
0
1
Order By: Relevance
“…In a large, multistate survey of adolescents, psychosocial surveillance was far more likely if either the clinician arranged to have at least part of the visit private or the adolescent knew how to confidentially arrange a visit with a clinician (5). Likewise, a survey of physicians in New York found that those who made more of their adolescent visits private also provided more tobacco surveillance and counseling (47). A nationally representative survey of family physicians and pediatricians, however, found that only 64% of physicians often or always saw adolescents without their parents present (11).…”
Section: Lack Of Privacy For Adolescentsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a large, multistate survey of adolescents, psychosocial surveillance was far more likely if either the clinician arranged to have at least part of the visit private or the adolescent knew how to confidentially arrange a visit with a clinician (5). Likewise, a survey of physicians in New York found that those who made more of their adolescent visits private also provided more tobacco surveillance and counseling (47). A nationally representative survey of family physicians and pediatricians, however, found that only 64% of physicians often or always saw adolescents without their parents present (11).…”
Section: Lack Of Privacy For Adolescentsmentioning
confidence: 99%
“…Large surveys suggest that longer visit times with both young children and adolescents are associated not only with increased developmental or psychosocial surveillance and anticipatory guidance, but also with parent satisfaction (31,40,47,65,86). Likewise, a panel of childhood injury-prevention experts concluded that time may be one of the most important requirements for providing guidance (19).…”
Section: Clinician and Patient Gender-related Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2 studies that assessed counseling of adolescent patients, physicians reported screening 71.4% of younger adolescents and 84.8% of older adolescents about tobacco use in a California survey 25 and 91% of adolescents in an upstate New York survey. 26 In a study of Connecticut physicians and dentists, 65% of practitioners reported "frequently" or "always" counseling patients about tobacco between ages 16 and 18, 54% between ages 13 and 15, and 38% between ages 10 and 12. 27 With respect to parent counseling, a study in Vermont found that 94% of pediatricians surveyed reported that they advised at least 60% of their smoking parents to quit, 12 and a similar study in Maine found that 91% of pediatricians reported that they advised their smoking parents to quit.…”
mentioning
confidence: 99%
“…7,8 In a study, information and education activities of health workers in health facilities were considered key contributors to the changes in reported behaviors of the adolescents. 9 Most studies suggest that access to all settings can be improved through youth-friendly interventions. [10][11][12] In the present study too, there was statistically significant (P<0.05) improvement in the knowledge of adolescents on different aspects of ARSH issues [except the knowledge on male reproductive organ among boys in clinic-based and school-based study (P > 0.05) and knowledge on oral pills among boys in school-based study (P > 0.05)] following sensitization programme in youth friendly manner maintaining privacy, confidentiality and non-judgmental approach.…”
Section: Discussionmentioning
confidence: 99%